Damages sustained by agricultural lands in Wyandotte County from the Flood of 1903 - Groves, Charles Alfred (My University, 1904)
Introduction: Perhaps never before in the history of the famous Kaw Valley has such a disaster been sustained by the farmers in that valley as resulted from the great flood, May 28th to June 5th, 1903. The Grass-hoppers have swept over the land seeking what may, and may not be devoured; late frosts have laid low the crops, and while these wrought great ills upon the pocket-book, the land was left intact; but why should we be so astonished at this most natural happening. Way back in physical geography or structural geology we learned that every river had a flood plain, built up by deposits of its own waters. Certainly the Kaw, with its low banks, not with-standing our dis-regard for geological facts before the '03 flood, could not evade this natural law, but on the contrary, during the early formation of this noted river plain, floods were of more frequent and extensive occurance. According to Indian Tradition, three floods occured on this plain, in the nineteenth century, viz: 1811, '22 and '44, and since the '03 flood we are inclined to give full credence to these traditions.
Flood damages to agricultural land in Wyandotte County
Citation: Groves, Charles Alfred. Damages sustained by agricultural lands in Wyandotte County from the Flood of 1903. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Floods; Natural Disasters; Kansas; Wyandotte County; Theses